2015
DOI: 10.4049/jimmunol.1500387
|View full text |Cite
|
Sign up to set email alerts
|

MAZR and Runx Factors Synergistically Repress ThPOK during CD8+ T Cell Lineage Development

Abstract: Th-inducing Pox virus and zinc finger/Krüppel-like factor (ThPOK) is a key commitment factor for CD4+ lineage T cells and is essential for the maintenance of CD4 lineage integrity; thus, the expression of ThPOK has to be tightly controlled. In this article, we demonstrate that Myc-associated zinc finger-related factor (MAZR) and Runt-related transcription factor 1 (Runx1) together repressed ThPOK in preselection double-positive thymocytes, whereas MAZR acted in synergy with Runx3 in the repression of ThPOK in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 33 publications
(54 reference statements)
2
39
0
1
Order By: Relevance
“…). Recently, synergic functions of MAZR and Runx in repressing Thpok and Cd4 genes was reported , further confirming that these two proteins could form functional complexes on these silencers. It was also reported that Bcl11b transcription factor is involved in Thpok repression in precursor DP thymocytes , as the Thpok gene is de‐repressed from those cells upon inactivation of the Bcl11b gene by the Cd4‐Cre transgene.…”
Section: Thpok Silencer: the Right Place To Meet Tcr Signals In The Bmentioning
confidence: 70%
“…). Recently, synergic functions of MAZR and Runx in repressing Thpok and Cd4 genes was reported , further confirming that these two proteins could form functional complexes on these silencers. It was also reported that Bcl11b transcription factor is involved in Thpok repression in precursor DP thymocytes , as the Thpok gene is de‐repressed from those cells upon inactivation of the Bcl11b gene by the Cd4‐Cre transgene.…”
Section: Thpok Silencer: the Right Place To Meet Tcr Signals In The Bmentioning
confidence: 70%
“…Among them, the thymic enhancer ( TE ), located upstream of the Sth , acts first to initiate Thpok expression 21 , which is subsequently upregulated through the activity of a proximal enhancer ( PE ) locating 1.8 kb downstream of the proximal P2-promoter 22 . While factors that regulate Sth activity, such as Runx family proteins 19 and MAZR 23 , 24 , have been identified, the factors involved in the activation of TE and PE remain poorly characterized. Gata3 25 and Tcf1/Lef1 26 regulate Thpok expression, but primarily do so by targeting other regulatory regions such as general T-lymphoid enhancer, the known third enhancer.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of Mazr, Thpok was derepressed in DP thymocytes, leading to lineage redirection of MHC class I selected thymocytes into the helper lineage. The derepression of Thpok was enhanced when combined with mutations in Runx1 or Runx3 (131). CD4 derepression was also enhanced in DN thymocytes doubly deficient for Runx proteins and Mazr, supporting a cooperative role between these factors (131).…”
Section: Cis Elements and Epigenetic Regulation Of The Cd8 Locusmentioning
confidence: 99%
“…The derepression of Thpok was enhanced when combined with mutations in Runx1 or Runx3 (131). CD4 derepression was also enhanced in DN thymocytes doubly deficient for Runx proteins and Mazr, supporting a cooperative role between these factors (131). Mazr likely regulates Thpok expression directly as it was found to bind the Thpok silencer element (130).…”
Section: Cis Elements and Epigenetic Regulation Of The Cd8 Locusmentioning
confidence: 99%